The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/1521-3765(20020715)8:14<3277::aid-chem3277>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Methane Activation and Oxidation in Sulfuric Acid

Abstract: In a versatile modular scaffold system, gradient nonwovens of in situ crosslinked gelatin nanofibers (CGN), fabricated by reactive electrospinning, are laminated with perforated layers and nonwovens of thermoplastic non‐crosslinked biodegradable polyesters. The addition of glyoxal to a gelatin solution in a non‐toxic solvent mixture consisting of acetic acid, ethyl acetate, and water (5:3:2 w/w/w) enables the in situ crosslinking of gelatin nanofibers during electrospinning. The use of this fluorine‐free cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Formic acid is a flat organic molecule, the average length of O5C-O-H bonds is 0.171 nm, the length of O5C-C-H bonds are 0.224 nm (Stein and Sauer, 1997;Goeppert et al, 2002;Jarvis, 2003). The bond length of hydrochloric acid is 0.128 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Formic acid is a flat organic molecule, the average length of O5C-O-H bonds is 0.171 nm, the length of O5C-C-H bonds are 0.224 nm (Stein and Sauer, 1997;Goeppert et al, 2002;Jarvis, 2003). The bond length of hydrochloric acid is 0.128 nm.…”
Section: Discussionmentioning
confidence: 99%
“…H/D exchange was observed when methane was recirculated in D 2 SO 4 at temperatures of 250 C and above and an apparent activation energy of 176 kJ mol À1 was measured. 18 In the strongest superacid, HF-SbF 5 , we experimentally determined that the secondary kinetic isotopic effect for the H/D exchange, k(CH 4 )/k(CH 3 D), is very close to unity; 19 moreover, high level computational studies using H 2 F þ , more or less solvated by excess HF as the superacid species, suggested that CH 5 þ was not an intermediate in the exchange reaction but acted rather as a part of the activated complex strongly solvated by (HF) x . 19 The apparent activation energy of 75 kJ mol À1 measured by Hogeveen and Gaasbeek 9 shows the large difference of stability of this activated complex between strong acidic media and superacid media.…”
Section: Introductionmentioning
confidence: 98%
“…Theoretical calculations are also performed to assist in the establishment of possible mechanisms for the carboxylation of methane, an approach that had not yet been previously addressed in detail for such a type of system. Although a number of mechanistic proposals have been recently considered for alkane hydroxylation, halogenation, and dehydrogenation reactions, of methane oxidation in sulfuric acid and on an Fe-exchanged zeolite, of activation of C−H bonds of alkanes by platinum, titanium, and lanthanide complexes, by dirhodium tetracarboxylate, by unsaturated aluminum ions, by Sc + cation, by metal oxides, etc., to our knowledge, there are only a few publications where possible mechanisms of alkane carboxylation were proposed ,,,,, and only one case with detailed theoretical calculations 34b that has been reported and in a system different from ours.…”
Section: Introductionmentioning
confidence: 99%